Pere Marquette : A Michigan Railroad System before 1900 - Meints, Graydon M. (Book collections on Project MUSE., 2020)
"The Pere Marquette Railroad was formed in 1900 as the merger of three Michigan railroad companies. This work considers the nineteenth-century predecessors of the three companies, the reason for building the parts of the system, the success of the parts and their predecessors, and eventual need of the companies to consolidate"--